Is it safe to exercise during oncological treatment? A study of adverse events during endurance and resistance training – data from the Phys-Can study. (2nd January 2021) - Henriksson, Anna; Johansson, Birgitta; Radu, Calin; Berntsen, Sveinung; Igelström, Helena; Nordin, Karin
Abstract: Introduction: Few studies have systematically evaluated the risk of adverse events (AEs) among persons exercising during oncological treatment. We aimed to describe incidence and types of AEs during exercise for persons undergoing oncological treatment, and associations to exercise intensity, exercise adherence, chemotherapy treatment, initial aerobic fitness. A second aim was to compare incidence of lymphedema, periphery inserted central catheter (PICC) complications, and other new medical conditions (any illness or injury occurred during the exercise trial) between high-intensity vs low-to-moderate exercise and usual care (UC). Methods: This descriptive, comparative study was based on data from an observational study including patients in an UC setting ( n  = 90) and a randomized exercise trial ( n  = 577) in which participants exercised at high-intensity (HI) or low-moderate intensity (LMI). Persons with breast, prostate, or colorectal cancer undergoing neo/adjuvant treatment were included. AEs were reported by exercise coaches, participants, and identified in medical records, as were lymphedema, PICC-complications, and new medical conditions. Results: Coaches reported AEs for 20% of the participants, while 28% of participants self-reported AEs. The most common coach- and participant reported AEs were musculoskeletal and the majority (97%) were considered minor. HI had higher likelihood of AEs than LMI, according to both coaches (OR: 1.9 [95%CI 1.16–3.21], p =.011) and participants (OR: 3.36 [95%CI 2.00–5.62], ≤ .001). Lymphedema rates were low (4-9%) and PICC complications ranged from 15% in LMI to 23% in UC and there were no statistically significant differences between HI, LMI, and UC. There were no statistically significant differences between HI and LMI regarding new medical conditions. Conclusions: Exercise during treatment is safe for these patient groups in this setting, even HI exercise can be recommended if no medical contraindications are present. Similar to healthy populations, a higher risk of having minor AEs when exercising at HI in comparison to LMI may exist.